Framing and integration in the global forest, agriculture and climate change nexus. (December 2018) - Soto Golcher, Cinthia; Visseren-Hamakers, Ingrid J
This article contributes to the debate on Integrative Governance by studying integration in the global forest–agriculture–climate change nexus. Since the 1990s, the role of the land-use sector, in particular forests and agriculture, has become increasingly prominent in climate change debates due to its vulnerability and its contribution to global greenhouse gas emissions. Addressing agriculture, climate change and forest policies in an integrated way could therefore create important synergies and reduce trade-offs. This article aims to analyse the extent of integration in current global governance in the nexus of agriculture, forests and climate change, and to explain this extent of integration. Based on the analysis of secondary data, participation in key events and semi-structured interviews, this article concludes that efforts to enhance integration have taken different forms for the different pairs of domains (climate change–agriculture, agriculture–forest, forest–climate change) as well as for the nexus of the three. Integration has been mainly enhanced through soft law, programmes and integrative approaches (e.g. landscape approach, climate smart agriculture, agroforestry). The analysis also shows that the extent of integration among the governance systems has differed. Interplay management efforts on forests and climate change have been relatively successful. Agriculture and forest, and agriculture and climate have low and modest levels of integration respectively, except adaptation in agriculture, which enjoys higher integration levels. Differences in integration can be explained by the medium to high degrees of legalization and the (in)compatibility of the dominant frames present in the different governance systems. Furthermore, our results show that integration in a governance system with a high degree of legalisation, and dominated by one regime, as is the case in climate change, presents important challenges. In such cases, integration might have greater potential outside the intergovernmental regime through soft law approaches.